Localized de novo phospholipid synthesis drives autophagosome biogenesis. Issue 4 (2nd April 2020) - Schütter, Maximilian; Graef, Martin
ABSTRACT: During (macro)autophagy, cells form transient organelles, termed autophagosomes, to target a broad spectrum of substrates for degradation critical to cellular and organismal health. Driven by rapid membrane assembly, an initially small vesicle (phagophore) elongates into a large cup-shaped structure to engulf substrates within a few minutes in a double-membrane autophagosome. In particular, how autophagic membranes expand has been a longstanding question. Here, we summarize our recent work that delineates a pathway that drives phagophore expansion by localized de novo phospholipid synthesis. Specifically, we found that the conserved acyl-CoA synthetase Faa1 localizes to nucleated phagophores to locally activate fatty acids for de novo phospholipid synthesis in the neighboring ER. These newly synthesized phospholipids are then preferentially incorporated into autophagic membranes and drive the expansion of the phagophore into a functional autophagosome. In summary, our work uncovers molecular principles of how cells coordinate phospholipid synthesis and flux with autophagic membrane formation during autophagy. Abbreviations: ACS: acyl-CoA synthestases; CoA: coenzyme A; ER: endoplasmic reticulum